Reflections: Complex adaptive management and sustainable development (Ágora de Heterodoxias, 2026)
In this session of reflections, we interviewed Jesús López, professor at the Center for Development Studies, Central University of Venezuela (CENDES-UCV), about the scope of his proposal on Complex Adaptive Management (CAM), its usefulness in creating sustainable futures, and his considerations on the experiments carried out related to sustainable social transformation and its implications for sustainable development.
Keywords: Complex adaptive management; sustainable development; social transformation